Modelos estruturais e organizacionais no processo civil : uma nova perspectiva dos critérios de distribuição dos poderes processuais - Oliveira, Guilherme Botelho de (2017)
The purpose of the study is to examine the structure and organization of the civil process and the various models or types of structure that can be formed from culture. From the insertion of law as a product of social adaption, it was sought to demonstrate that since procedural law is the branch closest to life, culture is not infamous. In the first part examines the origin and evolution of the dispositive principle in order to reach its real content and contemporary extension. In order to achieve this, the content of its opposite principle (the inquisitorial) was drawn from its construction in criminal law. Firstly, the division of the dispositive principle and the debate of the German doctrine of the eight hundred is exposed, and its content and extension are limited. Already in the second part of the thesis, based on the premises established in the first one, the two most well-known models of organization of the civil process are presented, namely the adversarial model, the Reactive States and the social model (non-adversarial), drawing their differences from historical and political factors. The ideological debate that over the last decade formed these two systems is still presented and surpassed today. Before closing this part of the study, other possible organizational models are seen from historical experience. Countries of socialist economy; and the so-called cooperative model of civil procedure. Finally, in the last part of the study, the division and classification of individual and transindividual rights is exposed in order to demonstrate the inapplicability of the principle of demand (or dependence on the will of the interested party) to the latter. From the universalization of procedural conventions in the CPC of 2015, the political-legislative option of granting greater autonomy to the parties in some types of litigation is highlighted, with a reading of art. 370 of the CPC, which provides the power to determine ex official evidence by the judge to only focus on cases where there are no fully capable parties or litigation over rights that do not allow self-determination, or even when the parties are not in a situation of Negotiating parity.